Pembuatan Permainan Monopoly dengan Pelajaran Matematika di Android dengan Menggunakan Unity - Fendy Nyoto Koeshariyanto; Gregorius Satia Budhi (Jurnal Infra, 2016)
School teachers and the parents often say the importance of learning mathematics that can make students / student elementary school (elementary school) can count without a calculator. Although the student / student had been told that, they still think that math is very difficult and not necessary to hold these lessons to any school level. This makes the student / student always assume that things are difficult does not need to exist and refurbished.In making this application is done prior research interest in learning the students / student elementary school in math, so that the expected results can help students' learning motivation / elementary school. Manufacture of their objects more emphasis to entice young children to learn and play. Giving collision feature aims to allow users to switch pages one page to another. The use of smartphones with Android OS (Operating System) aims to facilitate the student / student can play and learn while they are playing smartphone.The results in this application, any object found on each page have made the learning interest of the students / student elementary school is more increased than before. Barriers time of making a major factor, so it can not make every page more detail. Disadvantages of this application, requires specification of the smartphone that is high enough to be able to run applications MathVenture well. This is because the design of each page makes heavy use more memory.